Growth and Maintenance of Barramundi (Lates calcarifer) Fed with Commercial Feed at BPBAP Situbondo - Andriana, Ina Eka; Diamahesa, Wastu Ayu (Program Studi Budidaya Perairan Universitas Mataram, 2025)
This study evaluated the growth performance and maintenance of white seabass (Lates calcarifer) fed with commercial feed at BPBAP Situbondo. As a high-value aquaculture commodity with increasing market demand, white seabass farming faces challenges in seed production and growth optimization. The research monitored growth parameters, survival rate (SR), and water quality during a 4-month rearing period (February-June 2024) in concrete tanks (2.5×4×1.2 m). Results showed that commercial feeds (Megami/Skretting) administered via ad-satiation method (3-4x/day for juveniles <7cm, 2x/day for 8-14cm fish) supported growth, though size variation triggered cannibalism. Water quality parameters remained optimal (pH 7.49-8.17; salinity 33-34‰; ammonia 0.011-0.026 mg/L) per SNI 8036:2014 standards, contributing to an 83.98% SR. Key findings emphasize the critical role of routine grading to prevent cannibalism, strict feed management to minimize toxic waste accumulation (TAN peaked at 1.397 mg/L), and daily water exchange (100% replacement). The study concludes that integrated feed-water management significantly enhances white seabass productivity, recommending further research on nutrient-specific feed formulations and advanced filtration systems to address the 16% mortality rate.